The Effectiveness of Repetitive Transcranial Magnetic Stimulation on Resilience and Negative Meta-Emotion in Infertile Women with Obsessive–Compulsive Disorder - Zorrieh, Saloomeh; Rahmanian, Mahdieh; Rafiepoor, Amin (Psychology of Woman Journal, 2026)
The present study aimed to determine the effectiveness of repetitive transcranial magnetic stimulation (rTMS) on resilience and negative meta-emotion in infertile women with obsessive–compulsive disorder (OCD). This quasi-experimental research employed a pretest–posttest control-group design with a three-month follow-up. The statistical population comprised all infertile women with OCD who attended treatment centers in Tehran in 2024. Participants were randomly assigned to experimental and control groups. Before the intervention, all participants completed the Connor–Davidson Resilience Scale (CD-RISC; 2003). The experimental group then received an rTMS intervention delivered in six weekly 90-minute sessions. Data were analyzed using repeated-measures ANOVA. Results indicated a significant difference between pretest and posttest across groups (p < .05). Additionally, for both resilience and negative meta-emotion, significant between-group differences were observed at posttest and at follow-up (p < .05). These findings suggest that rTMS can effectively enhance resilience and reduce negative meta-emotion in infertile women with OCD.